Diagnóstico dos resíduos gerados em estações de tratamento de água nas bacias dos rios Piracicaba, Capivari e Jundiaí - SP - Vilella, Alexandre Luis Almeida (2011)
The basins of Piracicaba, Capivari and Jundiaí has a territory of 15,304 square kilometers, about 5.2 million inhabitants, 7% of gross national product. However, the scarcity of water resources threatens all this prosperity. The uses of water have led to conflicts because of its multiple and diverse purposes, which require different quantities and qualities. It is against this background that becomes fundamental to understand the current situation of water supply and waste management from the treatment process. The mobilization of society, awareness of public officials and increase the availability of financial resources for the sanitation sector have provided the municipalities to increase their rates of water treatment, through the construction of new structures and technological innovations, however, has aroused another focus attention to the urgent need for the systemic management of waste from water treatment plants, especially the generation, treatment and disposal of sludge and its actual and potential environmental impacts. This research has made diagnosis of generation under the quantitative aspect of the sludge generated in the 89 water treatment plants operating in 58 cities, and identify some experiences about the management. Through various methodological tools, such as the use of questionnaires for data collection to obtain primary data, the paper presents and discusses information about the current generation of waste, existing experiences regarding the disposal and treatment, and the challenges issue requires to be addressed. The results pointed that 9013.20 tons of monthly dry solids are generated, with prominence the one that 70% of plants in operation don't possess any of measurement of the muds system. The realities, front to the service of the effective legislations, training lack and the managers systemic administration and operators on the theme as well as the need of the integration of the sectorial politics with the operation of the systems of water supply that are the great challenges to be overcome.